Impacts of oxalic acid-activated phosphate rock and root-induced changes on Pb bioavailability in the rhizosphere and its distribution in mung bean plant. (1st July 2021) - Rasool, Bilal; ur-Rahman, Mahmood; Adnan Ramzani, Pia Muhammad; Zubair, Muhammad; Khan, Muhammad Asaf; Lewińska, Karolina; Turan, Veysel; Karczewska, Anna; Khan, Shahbaz Ali; Farhad, Muniba; Tauqeer, Hafiz Muhammad; Iqbal, Muhammad
Abstract: Rhizosphere acidification in leguminous plants can release P from the dissolution of phosphate compounds which can reduce Pb bioavailability to them via the formation of insoluble Pb compounds in their rhizosphere. A soil polluted from Pb-acid batteries efﬂuent (SPBE), having total Pb = 639 mg kg −1, was amended with six different rates (0, 0.5, 1, 2, 4 and 6%) of oxalic acid-activated phosphate rock (OAPR) and their effects on pH, available P and bioavailable Pb concentrations in the rhizosphere and bulk soils of mung bean plant were evaluated. Furthermore, the effects of these variant OAPR rates on Pb concentrations in plant parts, bioaccumulation factor (BAF) and translocation factor (TF) for Pb in grain and traits like productivity, the activities of antioxidant enzymes, and grain biochemistry were investigated. Results revealed that increasing rates of OAPR significantly increased pH values and available P while decreased bioavailable Pb concentrations in the rhizosphere over control. The highest dissolution of P in the rhizosphere was with 4 and 6% OAPR rates. As a result, the formation of insoluble Pb compounds affected on reduced Pb concentrations in shoots, roots, and grain in addition to lower grain BAF and TF values for Pb over control. Likewise, the highest plant productivity, improved grain biochemistry, high Ca and Mg concentrations, least oxidative stress, and enhanced soil alkaline phosphatase activity were found with 4 and 6% OAPR rates. The OAPR 4% rate is suggested for reducing grain Pb concentration, cell oxidative injury, and improving grain biochemistry in mung bean. Graphical abstract: Image 1 Highlights: Mung bean growth was evaluated on soil polluted from Pb-acid batteries efﬂuent (SPBE). SPBE was amended with six sole oxalic acid-activated phosphate rock (OAPR) rates. Rhizosphere acidification enhanced P dissolution from OAPR and immobilized Pb. The least bioavailable Pb in SPBE and plant concentrations were at 4 and 6% OAPR. OAPR 4 and 6% rates improved yield, grain biochemistry, and pared oxidative stress.